Comparison of the energy requirements of an experimental plow, a moldboard plow and a disk plow - Celik, Ahmet (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
Field experiments were conducted on a wheat stubble field to compare specific draft and energy uses of three different plows with three bottoms: an experimental plow (EP), a disk plow (DP) and a moldboard plow (MP). Plow draft, forward speed and fuel consumption measurements were made with a test tractor equipped with fuel transducer, three hitch point transducers, ground speed radar and data logger. The experiments were carried out at a constant depth (20 cm) and at three tractor forward speeds (4.5, 5.4 and 6.3 km h-1). The results indicated that the specific draft, drawbar power and fuel consumption were affected significantly by plows and speeds. Lowest draft and drawbar power were obtained for the moldboard plow (5.73 kN, 8.39 kW). Lowest specific draft and fuel consumption were obtained for the experimental plow (2.30 N cm -2, 14.96 L ha-1). Highest draft, specific draft, drawbar power and fuel consumption were obtained for the disk plow (9.59 kN, 4.15 N cm-2, 14.43 kW and 17.31 L ha-1, respectively). Draft, power and fuel consumption increased with increasing forward speeds. Overall energy efficiency of all plows ranged from 10-20%. The experimental plow was found to have the highest field efficiency.